2017
DOI: 10.21273/horttech03694-17
|View full text |Cite
|
Sign up to set email alerts
|

Screening Brassica Cultivars for Resistance to Western Oregon Clubroot Pathotypes

Abstract: Growing resistant cultivars from the Brassicaceae family (brassicas) is an effective strategy to minimize crop loss caused by the soilborne pathogen Plasmodiophora brassicae (clubroot). However, there are many clubroot pathotypes, and genetic resistance to clubroot may be pathotype-specific. To determine which pathotypes are present in western Oregon, diseased roots were collected from five farms and identified by the European clubroot differential (ECD) set. To assess resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several B. oleracea germplasm collections consisting of different morphotypes have been evaluated for clubroot resistance by various research groups, and several resistance sources have been identified. Fewer resistance accessions have been reported in cauliflower [ 51 , 52 , 53 , 54 ] compared to other B. oleracea varieties such as cabbage, kale, broccoli, brussels sprout, etc. [ 51 , 52 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Genomicsmentioning
confidence: 99%
“…Several B. oleracea germplasm collections consisting of different morphotypes have been evaluated for clubroot resistance by various research groups, and several resistance sources have been identified. Fewer resistance accessions have been reported in cauliflower [ 51 , 52 , 53 , 54 ] compared to other B. oleracea varieties such as cabbage, kale, broccoli, brussels sprout, etc. [ 51 , 52 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Genomicsmentioning
confidence: 99%